(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article analyzes the formation of Uzbek storytelling, its developmental stages, and the level of its scientific study. In particular, it highlights how the content, artistic features, genre nature, and stylistic features of Uzbek short stories were interpreted by scholars of different eras. The article pays special attention to the role of Uzbek short stories in reflecting social life, depicting the human psyche, the skill of creating artistic images, as well as issues of language and style. At the same time, the role of the short story genre in modern literature and its significance in the modern literary process are also highlighted. As a result of the research, the scientific study of Uzbek short stories is systematically summarized, and the relevance of research in this direction is justified. This article serves to summarize existing scientific views on the study of the short story genre in Uzbek literary studies, analyze them, and draw new scientific conclusions